Optimization of Extracellular Cellulose in Nata de Citrullus Using Natural Nitrogen Derived from Glycine max-Based Soybean Sprout Extract - Lovena Destawari; Flaura Rosalinda; Imroatin Maghfiroh; Mohammad Syehan Firdaus (Program Studi Teknologi Hasil Pertanian, 2026)
Watermelon rind (Citrullus lanatus) constitutes a substantial fraction of post-harvest agricultural waste in tropical countries, particularly Indonesia. Its carbohydrate-rich composition makes it a viable substrate for bacterial cellulose fermentation, specifically for the production of nata de Citrullus. However, the efficiency of cellulose biosynthesis by Acetobacter xylinum is critically constrained by the availability of nitrogen in the fermentation medium. This study investigated how varying concentrations of soybean sprout extract (Glycine max) as a natural nitrogen source influence the physicochemical properties and sensory characteristics of nata de Citrullus produced from watermelon rind. A completely randomized design (CRD) was employed with four treatment levels of soybean sprout extract concentration: 0% (A1, control), 10% (A2), 25% (A3), and 50% (A4), with four replications per treatment. Fermentation was conducted over 14 days under ambient conditions using A. xylinum as the inoculant. Key parameters evaluated included nata thickness, wet yield, final fermentation pH, and organoleptic quality (texture, flavor, aroma, and appearance). Results demonstrated a consistent and statistically meaningful positive relationship between soybean extract concentration and nata quality. The control treatment (0%) yielded no cellulose layer, confirming the indispensability of an exogenous nitrogen source. Treatment A4 (50%) produced nata with the greatest thickness (8.3 mm) and highest wet weight (301 g), accompanied by the most substantial decline in pH (from 4.2 to 2.7), indicating peak fermentative activity. Organoleptic evaluation by 25 panelists revealed predominantly favorable scores that increased significantly with soybean extract concentration for all four attributes (one-way ANOVA, p < 0.001), with A4 (50%) obtaining the highest mean scores (4.68–4.72 on a 5-point hedonic scale) and no significant difference from A3 (25%). Soybean sprout extract from Glycine max functions effectively as a natural, food-safe nitrogen source in nata fermentation, with concentration directly governing the quality of the final product. These findings support its adoption as a sustainable alternative to synthetic nitrogen compounds in functional food biotechnology.